Change in Left Ventricular Ejection Fraction With Coronary Artery Revascularization and Subsequent Risk for Adverse Cardiovascular Outcomes. (19th April 2022) - Velagaleti, Raghava S.; Vetter, Joy; Parker, Rachel; Kurgansky, Katherine E.; Sun, Yan V.; Djousse, Luc; Gaziano, J. Michael; Gagnon, David; Joseph, Jacob
Abstract : Background: Coronary revascularization is recommended to treat ischemic cardiomyopathy. However, the relations of revascularization-associated ejection fraction (EF) change to subsequent outcomes have not been elucidated. Methods: In 10 071 veterans (mean age 67 years; 1% women; 15% non-White) who underwent a first percutaneous coronary intervention (PCI) or coronary artery bypass grafting between January 1, 1995, and December 31, 2010, and had prerevascularization and postrevascularization EF measured, we calculated delta-EF (postprocedure EF–preprocedure EF). We related delta-EF as a continuous measure and as categories (≤−5, −5<delta-EF<0, delta-EF=0, 0<delta-EF<5, and delta-EF≥5) to death (using Cox regression) and heart failure hospitalization days (using negative binomial regression) in multivariable-adjusted models, for total sample, and PCI and coronary artery bypass grafting strata. Results: Over follow-up (mean/maximum 5/14 years) 56% died. Each 5% improvement in delta-EF was associated with statistically significant reductions in death and heart failure hospitalization days of 5% (95% CI, 3%–7%) and 10% (95% CI, 5%–15%), respectively, in the total sample and 6% (95% CI, 4%–8%) and 10% (95% CI, 5%–16%), respectively, in the PCI subgroup. Patients in the highest delta-EF category had 27% (95% CI, 19%–34%) lower mortality (30% [95% CI, 21%–37%] lower in PCI stratum) and ≈40% lower heart failure hospitalization days in total sample and PCI stratum, compared with those in the lowest category. Relations of delta-EF and outcomes in coronary artery bypass grafting subgroup did not reach statistical significance. Conclusions: Revascularization-associated EF improvement was associated with significant reductions in mortality and heart failure hospitalization burden, particularly in the PCI subgroup.